Collaborative Governance dalam Penanggulangan Banjir di Desa Sumput Kabupaten Gresik - Hilmy Asyam B.S; Tukiman Tukiman (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to determine and analyze how collaborative governance works in flood management in Sumput Village, Gresik Regency. Ansell and Gash's collaboration model (Islamy, 2018) explains that there are four important indicators for the success of a collaboration, namely institutional design that can function as a basic rule in implementing collaboration, and leadership as a mediator and facilitator in collaboration. Collaborative governance in flood management in Sumput Village includes the involvement of other parties in the implementation process. In this study, the data used were through interviews, observations, and documentation that may be analyzed qualitatively. The results of this study explain that the collaboration model in flood management in Sumput Village involves several parties, including the Gresik Regency Regional Disaster Management Agency (BPBD), the community, and the private sector. This study also explains that collaboration in flood management in Sumput Village has been running as desired so that the impact of flooding can be reduced, but in terms of implementation it is still not optimal because there are still many problems that need to be addressed such as public awareness and efforts to find the best solution.